2014
DOI: 10.2527/jas.2013-6910
|View full text |Cite
|
Sign up to set email alerts
|

The effects of immunological castration and corn dried distillers grains with solubles withdrawal on growth performance, carcass characteristics, fatty acid analysis, and iodine value of pork fat depots1,2

Abstract: A total of 1,360 pigs were used in a 125-d study to determine the effects of corn dried distillers grains with solubles (DDGS) withdrawal after immunological castration (Improvest, Zoetis, Kalamazoo, MI) on growth performance and carcass fat quality of pigs. Pens of male pigs (initially 24 kg) were randomly allotted by BW and castration method (physically castrated [PC] or immunologically castrated [IC] barrows) to 1 of 3 diets with 8 replications per treatment and 27 to 29 pigs per pen. Treatments were arrang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…In fact, Wood et al (2008) reported that at least 4 mm of difference are required to detect changes in the fatty acid profile. Moreover, in the current work, the time elapsed from the second vaccination to slaughter (54 d) could not be enough to modify fat composition according to the work of Asmus et al (2014).…”
Section: Fatty Acid Profile Of Subcutaneous and Intramuscular Fatmentioning
confidence: 77%
“…In fact, Wood et al (2008) reported that at least 4 mm of difference are required to detect changes in the fatty acid profile. Moreover, in the current work, the time elapsed from the second vaccination to slaughter (54 d) could not be enough to modify fat composition according to the work of Asmus et al (2014).…”
Section: Fatty Acid Profile Of Subcutaneous and Intramuscular Fatmentioning
confidence: 77%
“…Liver increase in IC pigs was also reported by a number of authors (Pauly et al, 2009;Asmus et al, 2014;Boler et al, 2014;Tavárez et al, 2014;Moore et al, 2016). As PC barrows have no testes, their steroid hormones are absent, allowing the liver to function more efficiently with regard to the metabolism of compounds such as skatole, thus affecting liver activity, which could influence liver weight.…”
Section: Organs and Testis Weight And Yieldmentioning
confidence: 54%
“…However, when pigs were immunized, they showed a tendency to have less marbling, probably because IC pigs spend most of their lives as intact males which deposit less fat (Asmus et al, 2014). IMF content was likely to decrease, especially when 5 mg kg -1 of RAC were added to the diet, probably due to rapid down regulation of the β-receptors in the fat tissue (Dunshea et al, 2005).…”
Section: Quality Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of physical (PC) and immunological (IC) castration of barrows on various pork belly and bacon characteristics has recently been reported (Boler et al 2012;Asmus et al 2014;Kyle et al 2014;Tava´rez et al 2014). Bellies from IC barrows have generally been reported to be leaner, thinner and with softer fat with higher UFA (Boler et al 2012;Tava´rez et al 2014), which may result in lower bacon-slicing yield (Kyle et al 2014).…”
Section: Sex Effectsmentioning
confidence: 99%